Prevalence and risk factors for colorectal neoplasia in a self-selected Vietnamese screening cohort undergoing self-funded colonoscopy - Huong Thi Thuy To; Nhu Thi Hanh Vu; Hong Nguyen Diem Tong; Dao Thi Anh Nguyen; Thu Dang Anh Phan; Dat Quoc Ngo; Toru Hiyama; Duc Trong Quach (PLoS ONE, 2026)
Objective Several studies have investigated colorectal neoplasia (CRN) in Vietnamese patients who present with lower gastrointestinal symptoms. However, data on subjects without symptoms is limited. This study aimed to determine the prevalence and risk factors for CRN in asymptomatic Vietnamese adults. Methods This was a prospective, cross-sectional, single-center study. Participants were consecutively recruited from asymptomatic individuals who were self-selected to undergo self-funded screening colonoscopy. CRN was defined as the presence of adenoma, sessile serrated lesions, or colorectal cancer. Advanced CRN included adenoma ≥ 1 cm, with villous features or high-grade dysplasia; sessile serrated lesion ≥ 1 cm or with dysplasia; traditional serrated adenoma; or colorectal cancer. Multivariable logistic regression was performed to identify independent risk factors for CRN, adjusting for age, sex, BMI, family history of colorectal cancer, smoking status, and alcohol consumption. Results There were 714 patients, with a median age of 51 (18–79 years) and a female-to-male ratio of 1:1.46. In this screening-attending cohort, the prevalence of overall CRN and advanced CRN were 26.2% and 9.0%, respectively. In the multivariate analysis, factors significantly associated with CRN included increasing age per 10-year increment (odds ratio [OR]: 1.76; 95% confidence interval [CI]: 1.47–2.11; p < 0.001), body mass index ≥ 23 kg/m 2 (OR: 1.70; 95% CI: 1.16–2.50; p = 0.006), alcohol consumption (OR: 1.83, 95% CI: 1.10–3.04, p = 0.020), and family history of colorectal cancer (OR: 2.43; 95% CI: 1.36–4.37; p = 0.003). Conclusions CRN was prevalent in this self-selected screening-attending cohort in a private clinical setting. Increasing age, overweight, and family history of colorectal cancer were independent factors associated with CRN.